Monetary Policy and Inequality in the UK - Haroon Mumtaz; Angeliki Theophilopoulou (Queen Mary University of London, School of Economics and Finance, 2015)
The UK has experienced a dramatic increase in earnings and income inequality over the past four decades. We use detailed micro level information to construct historical measures of inequality from 1968 to 2008. We study whether monetary policy shocks played a significant role in explaining this increase before and after 1993. We find that contractionary monetary policy shocks lead to a deterioration in earnings and income inequality and contribute to its fluctuation. Our evidence suggest that this effect is smaller during the inflation targeting period.
Keywords: E2; E3; E4; E5; 330; Inequality; Earnings; Income; Mixed frequency Bayesian SVAR; Monetary policy shocks